The Opportunities Swallow's Nest Business to Increase Community Income from Islamic Economics Perspective - Haris Al Reza; Mochammad Novi Rifa’i; Afifah Nur Millatina; Ascarya (University of Darussalam Gontor, 2023)
The swallow's nest business has a vast business opportunity, especially in areas that are crowded with swallows. Swallow's nests are very promising, but some obstacles and challenges must be faced. This study aims to find out how the swallow's nest business opportunity in increasing the income of the community in Kampung Baru village is viewed from the perspective of Islamic economics. This research uses a qualitative approach with the type of case study research. Sources of data in this study using primary data sources. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that Kampung Baru Village has the potential to conduct swallow's nest business in increasing the income of the community in Kampung Baru Katingan Kuala Village. This is evidenced by the increased income of SBW entrepreneurs, which is higher than the previous income when they had not built a swallow building. The increase in the revenue of the swallow's nest business can be seen from the rise in the swiftlet building owned by the swallow's nest entrepreneur, and the increasing level of education, as well as the increasing level of welfare of the people of Kampung Baru village through alms, infaq or donations. The Islamic economic perspective on the swallow's nest business is that no practices violate the Shari'ah that the swallow's nest entrepreneur has carried out. Efforts made by swallow entrepreneurs to increase people's income are reasonable efforts carried out with good intentions and efforts and are therefore in line with Islamic law.